2010
DOI: 10.1089/pho.2009.2586
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Repair Composite Resin to an Acid-Etched and a Laser-Irradiated Feldspathic Ceramic Surface

Abstract: HFA etching is the most effective surface treatment for increasing the shear bond strength between a repair composite resin and a feldspathic ceramic surface. The shear bond strength after laser irradiation can be increased by HFA etching, but the strength of the bond is still smaller than that after HFA etching alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 39 publications
3
49
3
Order By: Relevance
“…Cavalcanti et al 44 reported acceptable surface roughness by this laser at 400 and 600 mJ pulse energy. Akyil et al 40 showed that Er:YAG can be beneficial at 2 W power and 200 mJ pulse energy as well; the irradiation time for this setting was 10 seconds. CO 2 laser at 10 and 15 W power was used in the study of Ahrari et al and provided stronger bond strength than HF in feldspathic porcelains.…”
Section: Resultsmentioning
confidence: 96%
“…Cavalcanti et al 44 reported acceptable surface roughness by this laser at 400 and 600 mJ pulse energy. Akyil et al 40 showed that Er:YAG can be beneficial at 2 W power and 200 mJ pulse energy as well; the irradiation time for this setting was 10 seconds. CO 2 laser at 10 and 15 W power was used in the study of Ahrari et al and provided stronger bond strength than HF in feldspathic porcelains.…”
Section: Resultsmentioning
confidence: 96%
“…Previous reports have shown that the Er,Cr:YSGG laser is capable of producing surface roughness comparable to that produced by acid etching of enamel and dentin surfaces 37,38. Many studies have evaluated the effects of different surface treatments,12,15,39-41 including laser treatments,29,34,42-44 on the shear bond strength of resin cement to ceramic restorations. Shear bond strengths in Nd:YAG and Er:YAG laser-irradiated ceramic surfaces have also been investigated,44 but not in those treated with a Er,Cr:YSGG laser.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, previous studies have shown that surface roughening with Nd:YAG laser results in an increase in repair bond strength of indirect (12) and silorane-based composite resins (8). However, in a study by Akyil et al , use of Nd:YAG laser alone did not result in an increase in repair bond strength of feldspathic ceramic (19). The discrepancy between the results might be attributed to differences in substrates (composite resin or ceramic) and their different response to laser and also the differences in laser parameters.…”
Section: Discussionmentioning
confidence: 94%